Communities lead the sustainable management of the Nong Lom wetlands in Lao PDR - Inphonephong, Souphalack; Xaydala, Viengxay (International Water Management Institute, 2025)
IWMI, as part of the CGIAR Multifunctional Landscapes Program, organized a two-day training for members of the Nong Lom Wetlands management committee, with 27 participants, including 12 women in Hom and Tammaleuay villages, in Attapeu, Lao PDR. The training curriculum was developed in close consultation with community members and incorporated lessons from a farmer-to-farmer learning exchange in the Xiengkhouang Province, previously organized by IWMI and its partners. This consultative learning process helped clarify the roles of committee members and provided them with the knowledge they need to support the effective implementation of the Management Plan for the Nong Lom wetlands in the Attapeu Province (2024–2029), developed with support from IWMI and WorldFish under the previous CGIAR Initiative on Agroecology.